Methodical aspects of using riddles in the educational process of primary school children (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2014)
In the article the author proves that the enrichment of younger students’ vocabulary is one of the main ways to develop speaking skills, which plays a crucial role in the formation of linguistic identity. The role of riddles, as a genre of folklore, is determined in primary school students’ speaking education. Riddle-based tasks have been proposed.
Keywords: speaking development; linguistic identity; culture of communication; younger student; cognitive activity; riddle